2022
DOI: 10.1128/jvi.01560-21
|View full text |Cite
|
Sign up to set email alerts
|

A Panel of Kaposi’s Sarcoma-Associated Herpesvirus Mutants in the Polycistronic Kaposin Locus for Precise Analysis of Individual Protein Products

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) is the cause of several human cancers including the endothelial cell (EC) malignancy, Kaposi’s sarcoma. Unique KSHV genes absent from other human herpesvirus genomes, the “K-genes”, are important for KSHV replication and pathogenesis. Among these, the kaposin transcript is highly expressed in all phases of infection, but its complex polycistronic nature has hindered functional analysis to date. At least three proteins are produced from the kaposin transcript: Kapo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 111 publications
(183 reference statements)
0
6
0
Order By: Relevance
“…We individually transfected each plasmid and immunostained for each of the SARS-CoV-2 proteins using antibodies to the Strep-tag II and for PBs using anti-DDX6 (Figs 6A and S5). Relative to control cells, many SARS-CoV-2 ORF transfected cells still displayed DDX6-positive PBs; however, expression of some SARS-CoV-2 genes reduced DDX6-positive puncta, including N and ORF7b (Fig 6A ) to a similar or greater extent than our positive control, the KapB protein from Kaposi's sarcoma-associated herpesvirus, which we have previously shown causes PB disassembly (Fig 6B and 6C) [13,91,97,98]. We quantified the number of DDX6-positive PBs per cell for each transfection as in [91] and found that the average number of PBs per cell was reduced relative to our negative control after transfection of eight SARS-CoV-2 genes: nsp7, ORF7b, N, ORF9b, ORF3b, nsp6, nsp1, and nsp11 (Fig 6D and 6E).…”
Section: Plos Pathogensmentioning
confidence: 51%
“…We individually transfected each plasmid and immunostained for each of the SARS-CoV-2 proteins using antibodies to the Strep-tag II and for PBs using anti-DDX6 (Figs 6A and S5). Relative to control cells, many SARS-CoV-2 ORF transfected cells still displayed DDX6-positive PBs; however, expression of some SARS-CoV-2 genes reduced DDX6-positive puncta, including N and ORF7b (Fig 6A ) to a similar or greater extent than our positive control, the KapB protein from Kaposi's sarcoma-associated herpesvirus, which we have previously shown causes PB disassembly (Fig 6B and 6C) [13,91,97,98]. We quantified the number of DDX6-positive PBs per cell for each transfection as in [91] and found that the average number of PBs per cell was reduced relative to our negative control after transfection of eight SARS-CoV-2 genes: nsp7, ORF7b, N, ORF9b, ORF3b, nsp6, nsp1, and nsp11 (Fig 6D and 6E).…”
Section: Plos Pathogensmentioning
confidence: 51%
“…We individually transfected each plasmid and immunostained for each of the SARS-CoV-2 proteins using antibodies to the Strep-tag II and for PBs using anti-DDX6 (Fig 6A, S5). Relative to control cells, many SARS-CoV-2 ORF transfected cells still displayed DDX6-positive PBs; however, expression of some SARS-CoV-2 genes reduced DDX6-positive puncta, including N and ORF7b (Fig 6A) to a similar or greater extent than our positive control, the KapB protein from Kaposi’s sarcoma-associated herpesvirus which we have previously shown causes PB disassembly (Fig 6B, C) [13,91,97,98]. We quantified the number of DDX6-positive PBs per cell for each transfection as in [91] and found that the average number of PBs per cell was reduced relative to our negative control after transfection of eight SARS-CoV-2 genes: nsp7, ORF7b, N, ORF9b, ORF3b, nsp6, nsp1, and nsp11 (Fig 6D-E).…”
Section: Resultsmentioning
confidence: 72%
“…2002 ), but the preceding DR6 sequence encodes an important protein-binding domain of Kaposin B ( McCormick and Ganem 2005 ). Recently, it has been found that KSHV expressing Kaposin A only, without the Kaposins from IR2, establishes fewer episome copies during latency ( Kleer et al 2022 ). This effect may be attributed to the alteration of the GC-rich repeats in IR2, to be discussed later.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be attributed to the alteration of the GC-rich repeats in IR2, to be discussed later. Nevertheless, viruses lacking Kaposins retain the ability to reactivate and produce infectious virions ( Kleer et al 2022 ). Additionally, the expression of Kaposin B was unnecessary for KSHV-infected endothelial cells to assume spindle morphology ( Kleer et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation